High-Order Mesh Generation for Discontinuous Galerkin Methods Based on Elastic Deformation (Advances in Applied Mathematics and Mechanics, 2018)
In this paper, a high-order curved mesh generation method for DiscontinuousGalerkin methods is introduced. First, a regular mesh is generated. Second,the solid surface is re-constructed using cubic polynomial. Third, the elastic governingequations are solved using high-order finite element method to provide a fullyor partly curved grid. Numerical tests indicate that the intersection between elementboundaries can be avoided by carefully defining the elasticity modulus.